2014
DOI: 10.3892/mmr.2014.2973
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bile biomarkers of biliary tract cancer through a liquid chromatography/mass spectrometry-based metabolomic method

Abstract: Abstract. The incidence and mortality rate of biliary tract cancer have been increasing worldwide; however, its diagnosis and prognosis have not improved in recent years. A novel approach, termed 'metabolomics', may have the potential to be developed as an effective diagnostic tool. The present study prospectively obtained bile samples from 115 individuals, including 32 patients with biliary tract cancer, 61 patients with benign biliary tract diseases and 22 normal controls. A liquid chromatography/mass spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Significantly lower levels of LPC were evident in the bile of patients with biliary tract cancer compared to those with benign biliary tract disease [ 41 ]. Therefore, LPC may be a novel biomarker allowing early detection of biliary tract cancer [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Significantly lower levels of LPC were evident in the bile of patients with biliary tract cancer compared to those with benign biliary tract disease [ 41 ]. Therefore, LPC may be a novel biomarker allowing early detection of biliary tract cancer [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of deoxycholic acid (DCA) in CCA patients was reported to be lower than in patients with biliary tract stones or normal subjects 16 . Other research groups reported that the proportion of cholic acid (CA) and chenodeoxycholic acid (CDCA) was higher in patients with CCA than in BBD or hepatocellular carcinoma (HCC) 18 . Patients with CCA patients carry higher levels of taurine- and glycine-conjugated bile acids compared with patients diagnosed with BBD.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic cancer (PC) and biliary tract cancer (BTC) are highly aggressive cancers, for which the mortality rates closely parallel the incidence rates [ 1 ]. Most PC and BTC cases are not accompanied by clinical symptoms until the disease reaches an advanced stage [ 2 , 3 ]. A minority of PC and BTC patients present with surgically resectable disease, but the relapse rate is high [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%